1993
DOI: 10.1007/bf00405732
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of homovanillic acid in workers exposed to manganese

Abstract: Homovanillic acid, an end product of dopamine catabolism, and manganese (Mn) were measured in the urine of 68 male workers exposed to Mn-containing dust in a dry alkaline battery plant or an Mn oxide and salt producing plant, and in 35 control male subjects. The geometric mean of the airborne concentration of inhalable (total) dust amounted to 0.95 and 1.37 mg/m3 in the dry alkaline battery plant and the Mn oxide and salt producing plant, respectively. In the latter, a higher prevalence of increased values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Most of these studies were focused on work areas in manganese re®ning, steel production and welding processes whereas low-exposure situations such as dry cell manufacturing have been surveyed less frequently (i.e. Emara et al 1971;Roels et al 1992;Buchet et al 1993). …”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were focused on work areas in manganese re®ning, steel production and welding processes whereas low-exposure situations such as dry cell manufacturing have been surveyed less frequently (i.e. Emara et al 1971;Roels et al 1992;Buchet et al 1993). …”
Section: Introductionmentioning
confidence: 99%
“…Ellingsen et al (2003a,b) further suggested that the Mn-induced elevation of prolactin is generally within the reference limits and therefore is not suitable for use as a biomarker of Mn exposure. HVA, a catcholamine metabolite, is significantly increased in the urine of Mn-exposed welders (Ai et al 1998, Buchet et al 1993), yet a large fluctuation within control populations limits the use of HVA as an indicator of Mn exposure (Buchet et al 1993). …”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers of autonomic dysfunction reported for manganism include assays of serum dopamine hydroxylase and platelet monoamine oxidase (Smargiassi et al, 1995), urine homovanillic acid (Buchet, 1993), and serum prolactin (Mutti et al, 1996). Hyperhidrosis is a common autonomic symptom in manganism but the quantitation of the sweat response has not yet been evaluated in lesser exposures.…”
Section: Introductionmentioning
confidence: 99%